2014
DOI: 10.3390/rs61110813
|View full text |Cite
|
Sign up to set email alerts
|

Modeling and Mapping of Soil Salinity with Reflectance Spectroscopy and Landsat Data Using Two Quantitative Methods (PLSR and MARS)

Abstract: Abstract:The monitoring of soil salinity levels is necessary for the prevention and mitigation of land degradation in arid environments. To assess the potential of remote sensing in estimating and mapping soil salinity in the El-Tina Plain, Sinai, Egypt, two predictive models were constructed based on the measured soil electrical conductivity (ECe) and laboratory soil reflectance spectra resampled to Landsat sensor's resolution. The models used were partial least squares regression (PLSR) and multivariate adap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
67
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 136 publications
(85 citation statements)
references
References 64 publications
14
67
0
Order By: Relevance
“…Development of MARS models for soil salinity assessment was described in detail in Nawar et al [58,59]. In this study, the MARS analysis was performed using the ARESLab toolbox [77] with selected adaptations based on MATLAB 8.0 software.…”
Section: Multivariate Adaptive Regression Splinesmentioning
confidence: 99%
See 2 more Smart Citations
“…Development of MARS models for soil salinity assessment was described in detail in Nawar et al [58,59]. In this study, the MARS analysis was performed using the ARESLab toolbox [77] with selected adaptations based on MATLAB 8.0 software.…”
Section: Multivariate Adaptive Regression Splinesmentioning
confidence: 99%
“…It has been effectively applied in different fields [54][55][56][57] and generally exhibits very high performance compared with other linear and non-parametric regression models, such as principal component regression (PCR) and artificial neural networks (ANN). Nawar et al [58] used PLSR and MARS with soil spectroscopy and Landsat TM/ETM+ data for mapping soil salinity in El-Tina Plain in Egypt and reported that MARS provided better estimations for the soil salinity, yielding better cross-validation R 2 and ratio of performance to deviation (RPD) values than the generally used PLSR method did. The results of this study indicated a potential to extend the modeling capability of PLSR to model and map other soil properties and the need to test MARS models with other than Landsat multispectral data in order to prove their robustness.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A growing body of studies, aided by statistical analyses of field spectroscopy data and satellite remote sensing observations demonstrates that both multispectral [10][11][12][13][14][15] and hyperspectral passive reflectance data can be used to map soil salinization at landscape scales [16]. However, passive optical remote sensing based approaches may be hampered over coastal areas, black-clay soils, and desert areas, due to the smoothness and the white color of the formed crust [2].…”
Section: Introductionmentioning
confidence: 99%
“…Many studies using Landsat TM and ETM+ data have focused on drylands and on soil processes such as erosion and crusting [46,[48][49][50][51]. Very complex procedures, such as SMA, have been adopted to map degraded forests [52][53][54] or to estimate trends of fractional vegetation cover [55].…”
Section: Introductionmentioning
confidence: 99%